Does Extending the Waiting Time of Low-Rectal Cancer Surgery after Neoadjuvant Chemoradiation Increase the Perioperative Complications? - Kittinut Timudom; Natthawut Phothong; Thawatchai Akaraviputh; Vitoon Chinswangwatanakul; Ananya Pongpaibul; Janjira Petsuksiri; Suthinee Ithimakin; Atthaphorn Trakarnsanga (Gastroenterology Research and Practice)
Background. Traditionally, rectal cancer surgery is recommended 6 to 8 weeks after completing neoadjuvant chemoradiation. Extending the waiting time may increase the tumor response rate. However, the perioperative complication rate may increase. The purpose of this study was to determine the association between extending the waiting time of surgery after neoadjuvant chemoradiation and perioperative outcomes. Methods. Sixty patients with locally advanced rectal cancer who underwent neoadjuvant chemoradiation followed by radical resection at Siriraj hospital between June 2012 and January 2015 were retrospectively analyzed. Demographic data and perioperative outcomes were compared between the two groups. Results. The two groups were comparable in term of demographic parameters. The mean time interval from neoadjuvant chemoradiation to surgery was 6.4 weeks in Group A and 11.7 weeks in Group B. The perioperative outcomes were not significantly different between Groups A and B. Pathologic examination showed a significantly higher rate of circumferential margin positivity in Group A than in Group B (30% versus 9.3%, resp.; P=0.04). Conclusions. Extending the waiting to >8 weeks from neoadjuvant chemoradiation to surgery did not increase perioperative complications, whereas the rate of circumferential margin positivity decreased.